Healthcare Scenario: Health for All to Sustainable Development Goals - Kakkar, Rakesh; Aggarwal, Pradeep (Indian Journal of Community Health, 2019)
Poor quality care in public sector hospitals coupled with the costs of care in the private sector have trapped India's poor in a vicious cycle of poverty, ill health and debt for many decades. There is a huge cross section of the population that continues to struggle to gain access to affordable good quality healthcare. Although the rich can access healthcare by paying large sums of money, the poor are under major threat of financial duress. In Primary health care level public share is more with affordable cost but with compromised quality while in tertiary level private share is more with quality but at high cost and is focused in urban areas. Government has started spending at tertiary care level (newer AIIMS) to broaden the care spectrum but without much improvement at primary health care level. Accountable health care remains challenge for middle and low income countries. Accountability refers to “the principle that individuals, organizations and the community are responsible for their actions and may be required to explain them to others” (1). Low levels of public health financing, supply side gaps, an acute shortage of human resources and the rising cost of healthcare continue to severely affect access, affordability and quality of health services across the country. These issues make difficult for the public sector to remain accountable. The government has been attempting to address two main challenges: to ensure that all citizens can access healthcare equitably and to ensure that healthcare is made available at an affordable cost and without compromising on quality. So three important pillars for effective HCDS are cost, Access & Quality.